Quality Flaws: Issues and Challenges in Software Development - Mohan, P.; Shankar, A. Udaya; JayaSriDevi, K. (Computer Engineering and Intelligent Systems, 2012)
A statement “Prevention is better than cure” for illnesses in medical sciences also applies to the software development life cycle in terms of software defects. A defect is a deviation from actual functionality of the application in terms of the correctness and completeness of th e specification of the customer requirements. Defective software fails to meet its customer requirements leading to the development of appli cations with poor quality. Quality is a top priority in every enterpri se these days. Organizations struggle in a treadmill race to deliver q uality software to stay ahead with new technology, deal with accumulat ed development backlogs, handle customer issues as software teams work as hard as they can make their organizations stay alive and competiti ve in the market place. Software companies face an immense pressure to virtually release a bug-free product or a software package. The cultu re of an organization is a critical success factor in the efforts of p rocess improvement. The paper aims at assessing quality as a function for monitoring and measuring the strength of development processes and any successful application development enterprise requires an unambig uous understanding of customer expectation and maximizing participatio n of customers in the development activities thereby ensuring that peo ple involved in development activities do the right thing and do the t hing right for delivering high quality software . Keywords: Software d evelopment, process improvement, software defect, bug-free product, so ftware package